Pencegahan Peroksidasi Lemak dan Kerusakan Jaringan pada Tikus dengan Kitosan - Sri Raharjo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2000)
The present study focused on the effect of chitosan on oxidative status of rats fed with diets containing thermally oxidative palm oil. Forty-eight white male Sprague-Dawley rats weighing in the range of 90 to 105 g were fed with three different experimental diets ad libitum for up to 90 days. The first group was fed with a control diet containing 15 % fresh palm oil, the second group with the same diet except that the palm oil was thermally treated at 180° C for 24 hr, and the third group was fed with diet containing thermally treated palm oil and chitosan. Chitosan was added at 2 % level at the expense of fiber content. The experimental diets were analyzed for peroxide value, TBARS (2-thiobarbituric acid acids-reactive substances) and tocopherol content. Four rats from each dietary group were killed at time intervals of 30, 60 and 90 days of feeding and blood as well as tissue analyses were performed. Rats fed with diet containing thermally threated palm oil showed no significant differences in term of weight gain. TBARS level in serum, kidney, brain and heart as well as liver superoxide dismutase activity compared with other groups. However, rats fed with thermally treated palm oil had heavier liver weight, higher TBARS and lower vitamin E levels in liver. It seem that the addition of chitosan in the experimental diet could neutralize the negative effects of lipid oxidation products in the liver.